The Minute Virus of Canines (MVC) Activates the RhoA/ROCK1/MLC2 Signal Transduction Pathway Resulting in the Dissociation of Tight Junctions and Facilitating Occludin-Mediated Viral Infection - Xiang Ren; Zhiping Hei; Kai Ji; Yan Yan; Chuchu Tian; Yin Wei; Yuning Sun (Microorganisms)
The Minute Virus of Canines (MVC), belonging to the genus Bocaparvovirus within the family Parvoviridae, is associated with enteritis and embryonic infection in neonatal canines. Viral attachment to host cells is a critical step in infection, and viral protein 2 (VP2) as an important structural protein of MVC influences host selection and infection severity. Nevertheless, little is known about the interaction between VP2 protein and host cells. In this study, we identified that VP2 directly interacts with the kinase domain of RhoA-associated protein kinase 1 (ROCK1) by using mass spectrometry and immunoprecipitation approach and demonstrated that the RhoA/ROCK1/myosin light chain 2 (MLC2) signaling pathway was activated during the early stage of MVC infection in Walter Reed canine cell/3873D (WRD) cells. Further studies indicated that RhoA/ROCK1-mediated phosphorylation of MLC2 triggers the contraction of the actomyosin ring, disrupts tight junctions, and exposes the tight junction protein Occludin, which facilitates the interaction between VP2 and Occludin. Specific inhibitors of RhoA and ROCK1 restored the MVC-induced intracellular translocation of Occludin and the increase in cell membrane permeability. Moreover, the two inhibitors significantly reduced viral protein expression and genomic copy number. Collectively, our study provides the first evidence that there is a direct interaction between the structural protein VP2 of MVC and ROCK1, and that the tight junction protein Occludin can serve as a potential co-receptor for MVC infection, which may offer new targets for anti-MVC strategies.